Cost-effectiveness of cadonilimab plus chemotherapy in the first-line treatment of HER2-negative advanced gastric or gastroesophageal junction adenocarcinoma - Shixian Liu; Kaixuan Wang; Ruixue Wang; Hao Chen; Ziming Wan; Lei Dou; Shunping Li (Therapeutic Advances in Gastroenterology)
Background: The COMPASSION-15 clinical trial demonstrated that cadonilimab plus chemotherapy significantly improved clinical benefits in human epidermal growth factor receptor 2-negative (HER2−) advanced gastric or gastroesophageal junction (G/GEJ) adenocarcinoma. Objectives: This study investigated the cost-effectiveness of cadonilimab plus chemotherapy in the first-line treatment for HER2− advanced G/GEJ adenocarcinoma from the Chinese healthcare system perspective. Design: Economic evaluation. Methods: We compared three treatment regimens based on the COMPASSION-15 trial, including chemotherapy, cadonilimab plus chemotherapy, and programmed death ligand 1 (PD-L1) test-guided treatment. A partitioned survival model was constructed at 21-day cycle lengths over a 10-year time horizon to predict total costs, life-years, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratio (ICER) under the willingness-to-pay (WTP) threshold of three times the gross domestic product per capita ($40,334.05). Model parameters were obtained from a public bid-winning database and published literature. Scenario, one-way, and probabilistic sensitivity analyses were used to test the robustness of the model. Results: In the base case, the costs of chemotherapy, PD-L1 test-guided treatment, and cadonilimab plus chemotherapy were $7,207.78, $15,776.35, and $22,294.58, with QALYs of 0.59, 0.71, and 0.79, respectively. The ICERs of PD-L1 test-guided treatment and cadonilimab plus chemotherapy were $68,751.00 and $76,120.27 per QALY. The ICERs of cadonilimab plus chemotherapy were $58,469.16 and $121,123.92 per QALY for PD-L1 combined positive score (CPS) ⩾ 5 and <5 HER2− advanced G/GEJ adenocarcinoma. The cost of cadonilimab and patient weight were the most influential model parameters. Cadonilimab plus chemotherapy had a 0.01% cost-effectiveness in China. Conclusion: Cadonilimab plus chemotherapy might be a cost-effective regimen when the unit cost of cadonilimab was $151.48 (58% discount) and $188.04 (72% discount) for overall and PD-L1 CPS ⩾ 5 advanced G/GEJ adenocarcinoma.